Chemical mechanical polishing as an alternative surface treatment technique for corrosion prevention of carbon steel in an acidic medium - Ahmed, Mohamed; Al-Timimi, Buthainah Ali; Al-Ali, Maha; H. Abdullah, Ghassan; Atiyaha, Safa Khalaf; Aljanabi, Ahmed Yaseen Ali; Mel, Maizirwan (New Age - Media New Age Limited, 2025)
Chemical mechanical polishing (CMP) has been a standard technique in semiconductor manufacturing for achieving smooth surfaces. CMP utilizes a synergistic interplay of chemical and mechanical interactions to achieve the desired removal rates, selectivity, and ultimately planarity with different substrate materials. In this study, the impact of CMP on the surface properties of steel used in the petroleum industry was examined, with a focus on its corrosion behavior posttreatment. Steel samples were subjected to CMP with and without an oxidizer in a silica-based slurry, and their surface characteristics were compared to those of samples polished mechanically. The addition of an oxidizer to the slurry resulted in increased material removal rates and the formation of an oxide layer on the surface; this phenomenon was not observed in CMP without an oxidizer. However, in mechanical polishing, the action of silicon carbide grains on the steel surface led to an increase in the removal rate but caused a decrease in its corrosion resistance. Compared with other treatments, the oxide layer provided a good protective barrier against corrosion and improved the corrosion resistance of the steel substrate. Based on the results from the practical study, an improvement in the corrosion resistance properties was observed due to the chemical reaction of the oxidizer and the mechanical action of the silica nanoparticles; these results showed the importance of chemical mechanical polishing as an alternative method to reduce the corrosion of steel in acidic environments. Additionally, the effect of hydrogen peroxide in a silica slurry with respect to the wettability, surface roughness, and hardness of steel was examined using contact angle measurements, profilometry, scanning electron microscopy, and microhardness tests.